Freyana anatina (Koch, 1844) Feather mites (Acarina, Freyanoidea) recorded for the first time on wild ducks (Subfamily, Anatinae) in Turkey. - Aksin, Nursel (My University, 2007)
This study was performed to determine the presence of mite species on wild ducks (Subfamily, Anatinae) in Turkey. For this purpose, a total of 12 ducks were caught in the 2003-2004 hunting seasons and inspected for the presence of mite species. At the end of the examinations six ducks were found to be infested by mites. One mite species was found on the infested ducks. This species were identified as Freyana anatina (Koch, 1844). In coclusion, one species of mites not reported before in the mite fauna of Turkey were found.
Keywords: Animals; Bird Diseases; Ducks; Female; Larva; Male; Mite Infestations; Mites; Nymph; Sex Characteristics; Turkey; animal; animal disease; article; bird disease; classification; duck; female; histology; infestation; larva; male; mite; nymph; parasitology; sexual development; Turkey (republic)